New fluorescent electrospun polymer materials containing phenothiazinyl carboxylate metal salts for versatile latent fingerprint detection. (March 2023) - Gal, Melinda; Cristea, Castelia; Craciun, Ana Maria; Turza, Alexandru; Barbu-Tudoran, Lucian; Balazs, Brem; Lovasz, Tamas; Silaghi-Dumitrescu, Luminita; Gaina, Luiza Ioana
Abstract: In this work the synthesis and structural characterization by NMR and single crystal X-Ray Diffraction of four new phenothiazine-carboxylate salts (lithium, sodium, potassium, and calcium salts respectively) is reported together with a description of their use as contrast agents in the fabrication of new fluorescent electrospun polyvinylpyrrolidone nanomaterials suitable for latent fingerprint (LFP) detection were reported. The optical properties of the new fluorophores and fluorescent electrospun polymer (FEP) nanomaterials (λem = 448–467 nm) were evaluated by UV–Vis absorption/emission spectroscopy. Fluorescence lifetime imaging microscopy (FLIM) analysis indicated an intense and uniform fluorescence in solid state, with fluorescence lifetime increasing significantly for FEP material (8–11 ns) in comparison to the correspondent blank fluorophore. Scanning electron microscopy (SEM) investigations revealed the size of the new FEP materials situated in the nanometric range with fiber or granular morphology. The newly synthesized FEP nanomaterials were successfully tested in the detection of LFP from various smooth or porous surfaces such as glass, metal, plastic, ceramic or wood and demonstrated a versatile capability of direct visualization in UV and daylight of enhanced LFP, as well as of primary lifts collected by gently pressing the polymeric mats on the tested surfaces. The quality of the collected LFPs images was determined mainly by the fluorophore structure, best visualization results being obtained with the phenothiazine sodium carboxylate salt. The new FEP nanomaterials appear suitable for highly accurate forensic investigations, supporting a direct analysis by photography, an expeditive and non-hazardous alternative for avoiding the disadvantages of techniques such as dusting or chemical treatment currently applied in the dactyloscopic identification of a suspect person at the crime scene. Graphical abstract: Image 1 Highlights: New blue fluorescent 10-ethyl-10 H -phenothiazine-3-carboxylate salts (PC ). PC structure confirmed by single-crystal X-ray diffraction (XRD). New fluorescent electrospun polyvinylpyrrolidone with phenothiazine carboxylate. UV and daylight visualization of latent fingerprints (LFPs). Accurate LFPs sampling using FEP.